Kepemilikan Keluarga dan Penghindaran Pajak di Indonesia: Efek Moderasi dari Kualitas Audit - Tanujaya, Kennardi; Angelin, Angelin (E-Jurnal Akuntansi; Vol 32 No 11 (2022), 2022)
Tax avoidance is an action that can be taken by companies in an effort to reduce their obligation to pay taxes legally. Family and non-family companies have different characteristics in making tax avoidance decisions where family companies tend to prioritize the company's reputation in the future. This study aims to examine the effect of family ownership on the occurrence of tax evasion, as well as the role of audit quality in moderating this relationship. There are 777 companies listed on the Indonesia Stock Exchange from 2017 to 2021 as the study population. Companies that meet the sample criteria are 239 companies. The data analysis method used in this study is the panel regression method. The results showed that family ownership can influence ETR in a significant positive way. The effect of audit quality cannot strengthen the relationship between family ownership and tax evasion. Keywords: Tax Avoidance; Family Ownership; Audit Quality